Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11947-015-1566-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Oxygen Packaging on Tenderness and Water Holding Capacity of Pork Through Protein Oxidation

Abstract: The objective of this study was to investigate the biochemical difference of pork under high oxygen modified atmosphere packaging and their contribution to meat tenderness and water holding capacity of pork during postmortem storage. Twelve longissimus dorsi muscles were randomly assigned to either high oxygen modified atmosphere packaging or vacuum packaging and stored for 1, 4, and 6 days at 4°C. The carbonyl content, protein surface hydrophobicity, protein solubility, calpain activity, desmin degradation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 54 publications
4
43
0
Order By: Relevance
“…Cooking loss and compression loss are the primary indicators of WHC of meat (Chen et al ., ). The traditional cooking methods of spiced beef spend long time and significantly reduce the WHC of meat.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Cooking loss and compression loss are the primary indicators of WHC of meat (Chen et al ., ). The traditional cooking methods of spiced beef spend long time and significantly reduce the WHC of meat.…”
Section: Resultsmentioning
confidence: 97%
“…Simultaneously, the effects of ultrasonic treatment on the springiness and the chewing ability of spiced beef were not significant ( P > 0.05) while the resilience values were significantly lower ( P < 0.05), particularly at 120 min. The difference in muscle tenderness is mainly depended on the connective tissue, the myofibrillar components and integrity of muscle fibre in meat (Chen et al ., ). During the heating and cooking process, myofibrillar integrity of meat was destroyed in a certain extent and the tenderness was increased and also accompanied by a decrease in resilience values (Shigwedha, ).…”
Section: Resultsmentioning
confidence: 97%
“…Proteins are sensitive to oxidation, and studies have found that sarcoplasmic proteins, myofibrillar proteins (MP), and matrix proteins from red meat, poultry, and fish may be oxidatively damaged by lipids, metal ions, and other oxidants during meat processing (Chen, Zhou, & Zhang, ; Estévez, ; Lund, Heinonen, Baron, & Estevez, ; Soladoye, Juárez, Aalhus, Shand, & Estévez, ), thus greatly reducing their food quality and commodity value.…”
Section: Introductionmentioning
confidence: 99%
“…DL reflects decreased weight in samples as well as loss of some water‐soluble vitamins in the meat (Chen and others ).The DL of the exposed meat was mainly caused by weight loss. As shown in Figure , exposed samples showed a very high DL (mostly weight loss) of 30.9% on the 4th day and 55.4% at the end of storage period, far more than 2.7% to 3.7% and 8.3% to 9.1% of samples in other 4 cases ( P < 0.05), respectively.…”
Section: Resultsmentioning
confidence: 99%